Development of the Alhidayah Dictionary Application as a Digital Media for Arabic Language Research Terms - Nawang Wulandari (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2025)
In practice, many individuals still make errors when translating certain Arabic terms. These mistakes frequently occur in the translation of research-related terms, which often consist of two-word constructions. Such terms are commonly translated partially or word by word, resulting in inaccurate or misleading interpretations. Therefore, this study aims to develop a dictionary application of Arabic research terminology, particularly terms related to educational research. This application is named Alhidayah Dictionary. This study employs a Research and Development (R&D) methodology. The development model adopted in this research is the ADDIE model, developed by Reiser and Mollenda, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques used in this study include documentation and questionnaires. The questionnaires were utilized to assess product feasibility and to gather user responses. The collected data were analyzed using percentage-based statistical analysis. Based on the validation results from expert reviewers, which were subsequently converted using a media feasibility interpretation criteria table, the developed Alhidayah Dictionary application obtained a feasibility percentage of 79%. This result indicates that the application falls into the category of highly feasible. However, one limitation of this dictionary application is the requirement to pay an annual domain fee in order to maintain its accessibility. It is therefore expected that future researchers will be able to develop a more efficient and up-to-date dictionary application.